Scale and skills in European active management: Impact of a new regulatory context - Khim, Veasna; Razafitombo, Hery (Journal of Banking & Finance, 2023)
This study examines the impact of a new regulatory context on the dynamics and nature of returns to scale in European active management. Using a sample of 1325 actively managed European equity funds and following Pastor, Stambaugh, and Taylor’s model from 2015, we find strong evidence of industry-level decreasing returns to scale. We also find that the new regulatory context creates structural breaks in the optimal scale that significantly change the size-performance relationship. We find strong support that emerging and small-cap funds allow increasing returns to scale. We find evidence that fund families play a moderating role in decreasing returns to scale. Further, the results show a significant upward trend in fund skills evolution.